PREDICTION AND CONTROL OF AN INDUSTRIAL DEBUTANIZER COLUMN COMPOSITIONS USING ANN AND ANFIS TECHNIQUES - ANMOL, FATIMA (2021)
The debutanizer column in one of the refineries in Malaysia produces LPG as its top product and light naphtha as its bottom product.